2022
DOI: 10.1002/jcp.30913
|View full text |Cite
|
Sign up to set email alerts
|

Polystyrene nanoplastics aggravates lipopolysaccharide‐induced apoptosis in mouse kidney cells by regulating IRE1/XBP1 endoplasmic reticulum stress pathway via oxidative stress

Abstract: Nanoplastics (NPs) pollution poses a huge threat to the ecosystem and has become one of the environmental pollutants that have attracted much attention. There is increasing evidence that both oxidative stress and endoplasmic reticulum stress (ERS) are associated with polystyrene nanoplastics (PS‐NPs) exposure. Lipopolysaccharide (LPS) has been shown to induce apoptotic damage in various tissues, but whether PS‐NPs can aggravate LPS‐induced apoptosis in mouse kidneys through oxidative stress‐regulated inositol‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 51 publications
(63 reference statements)
0
2
0
Order By: Relevance
“…In a study by Sun et al, exposure to PS NPs (size 20 nm) resulted in collapse of ΔΨm, an event associated with the activation of cellular apoptosis, at TM3 mouse Leydig cells (Sun et al, 2023b). This finding was reinforced by studies showing increased expression of apoptosis-related proteins in cells exposed to MPs/NPs, providing further evidence that these particles may interfere with the role of mitochondria in the regulation of apoptosis (Li et al, 2021;Wang et al, 2022b;Li et al, 2023b). In addition, the interaction of MPs/NPs with mitochondria could also affect cellular calcium homeostasis, as calcium is critical for several mitochondrial functions, including ATP production, this disruption could have significant consequences for cellular health.…”
Section: Mitochondrial Toxicity Of Mps/npsmentioning
confidence: 94%
“…In a study by Sun et al, exposure to PS NPs (size 20 nm) resulted in collapse of ΔΨm, an event associated with the activation of cellular apoptosis, at TM3 mouse Leydig cells (Sun et al, 2023b). This finding was reinforced by studies showing increased expression of apoptosis-related proteins in cells exposed to MPs/NPs, providing further evidence that these particles may interfere with the role of mitochondria in the regulation of apoptosis (Li et al, 2021;Wang et al, 2022b;Li et al, 2023b). In addition, the interaction of MPs/NPs with mitochondria could also affect cellular calcium homeostasis, as calcium is critical for several mitochondrial functions, including ATP production, this disruption could have significant consequences for cellular health.…”
Section: Mitochondrial Toxicity Of Mps/npsmentioning
confidence: 94%
“…Investigating both HEK-293 cells and a murine in vivo model, Li et al showed that polystyrene NP can synergistically aggravate lipopolysaccharide (LPS)-induced renal cell apoptosis and the expression of the apoptosis markers Caspase-3 and Caspase-12 as well as endoplasmic reticulum stress through oxidative stress [50].…”
Section: Micro-and Nanoplastics Can Cross Well-controlled Barriers Of...mentioning
confidence: 99%
“…Most of the studies performed on nanoplastics (NPs) and MPs’ toxicity on kidney have been published in the last two years. Li et al showed that PS-NPs worsen lipopolysaccharide-induced apoptosis in mouse kidney cells through the oxidative stress–endoplasmic reticulum pathway [ 38 ]. Furthermore, Tang et al demonstrate nephrotoxicity in mice related to inflammation, oxidative stress and lipid disturbance [ 39 ].…”
Section: Microplastics Effects On Kidney Tissues and Cellsmentioning
confidence: 99%